Geographical distribution and evolutionary dynamics of H4Nx avian influenza viruses - Ge, Ye; Liu, Jing; Li, Yuanguo; Peng, Peng; Zhou, Yan; Yu, Jiantao; Huo, Miaotong; Liang, Xiaodong; Gao, Yuwei; Yao, Qiucheng (Frontiers in Microbiology, 2025)
H4Nx avian influenza viruses (AIVs) have been isolated from wild birds and poultry and can also cross the species barrier to infect mammals (pigs and muskrats). The widespread presence of these viruses in wild birds and poultry and their ability to be transmitted interspecies make them an undeniable hazard to the poultry farming industry. In the present study, we collected fecal and swab samples from wild birds and poultry in Guangdong Province from January 2019 to March 2024, and various subtypes of AIVs were isolated, including 19 strains of H4 subtype AIVs. Further analysis was conducted on the internal genes of the 19 strains. These strains clustered together with high homology to highly pathogenic avian influenza virus (HPAIV), suggesting that H4Nx AIV may be reassorted from HPAIV. Two H4N8 strains are phylogenetically related to the porcine H4N8 AIV. Molecular characterization revealed that all viruses in this study were less pathogenic but had potential mammalian-adapted mutations. The transmission dynamics of H4Nx AIVs revealed that Europe and Asia, especially the Netherlands and Bangladesh, may be the centers of transmission. This may be linked to the migration of wild birds. The high migration rates from Russia to the Netherlands and from Russia to Bangladesh may also play a role. Therefore, continuous and systematic monitoring of wild birds to clarify the spatial and temporal distribution and prevalence of influenza viruses in wild birds is significant for early warning of avian influenza outbreaks in poultry and for risk assessment for public health and safety.